Relative Effects of Isolated Combined and Complex Resistance Training on Selected Strength Speed and Power Parameters among College Men Students - D., Rajalakshmi; R. , Ramya; Pramanik, Amit (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study was to analyze the relative effect of isolated combined and complex resistance training on selected strength, speed, and power parameters among college men students. To achieve the purpose of the study, from the population of 40 college men students, those who have participated, and their age ranged from 16 to 19 years, height ranged from 160 to 168 centimeters, and weight ranged from 54 to 64 kilograms, were in a summer coaching camp conducted by the Sports Development Authority of Tamil Nadu, Thanjavur Unit, India. The selected participants were randomly assigned into four groups of ten participants each (n = 10). Group I underwent weight training (WT), group II underwent plyometric training (PT), group III underwent combined training (WPT) (weight and plyometric training), and group IV underwent complex resistance training (C*T). The purpose of the study was to analyze the relative effect of isolated combined and complex resistance training on selected strength, speed, and power parameters among college men students. To achieve the purpose of the study, from the population of 40 college men students, those who have participated, and their age of the subjects ranged from 16 to 19 years, height ranged from 160 to 168 centimeters, and weight ranged from 54 to 64 kilograms, were in a summer coaching camp conducted by the Sports Development Authority of Tamil Nadu, Thanjavur Unit, India. Static stability and dynamic movement testing were conducted for 4 experimental groups. To achieve the purpose of the study, testing is to determine the individual’s ability to stabilize the torso and control the body. In many cases, the larger and stronger muscles will cover up or hide weakness in the smaller stabilizing muscles. It is extremely important that the muscles of postural support are strong enough to withstand the stress of explosive training (Albert 1991). The basic static tests are followed in static stability testing. The difficulty can be increased by having participants being tested close their eyes for 30 seconds prior to the initiation of a plyometric program. The study concluded the training can be favorable for the selected variables in this study.